2015
DOI: 10.1002/phar.1644
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and Fecal Microbiota Transplant for Primary and Secondary Prevention of Clostridium difficile Infection

Abstract: Clostridium difficile infection (CDI) is the most common cause of nosocomial diarrhea and is associated with an increased risk of mortality. The use of probiotics and fecal microbiota transplantation (FMT) has been studied to reduce the incidence and severity of this infection, but variable efficacy and safety data have been reported. Probiotics are hypothesized to be effective in the management of CDI through a number of mechanisms that include maintenance of normal gastrointestinal flora, antimicrobial and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…One single‐center randomized open‐label study of adults with recurrent CDI demonstrated an 81% CDI cure rate with no relapse at 10 weeks using FMT versus 31% with oral vancomycin . Most studies regarding FMT do not include important details related to contribution of ICU patients, nor is there a comparative study that included FMT as a first‐line prevention strategy . The lack of FMT data for CDI prevention in the ICU is unfortunate because there is a signal of added benefit when implemented early, and gut diversity persists for several months after transplantation .…”
Section: Ancillary Strategies For CDI Preventionmentioning
confidence: 99%
See 3 more Smart Citations
“…One single‐center randomized open‐label study of adults with recurrent CDI demonstrated an 81% CDI cure rate with no relapse at 10 weeks using FMT versus 31% with oral vancomycin . Most studies regarding FMT do not include important details related to contribution of ICU patients, nor is there a comparative study that included FMT as a first‐line prevention strategy . The lack of FMT data for CDI prevention in the ICU is unfortunate because there is a signal of added benefit when implemented early, and gut diversity persists for several months after transplantation .…”
Section: Ancillary Strategies For CDI Preventionmentioning
confidence: 99%
“…The diverse microbiome of a healthy gastrointestinal environment provides colonization resistance against C. difficile and nourishment of endothelial cells by fatty acid production. 59 Disruption of the gut microbiota, typically from antibiotics active against anaerobic bacteria, compromises these defense mechanisms and enables overgrowth of microorganisms that induce diarrhea. The term antibiotic-associated diarrhea describes this common adverse effect of antibiotic treatment (5-30%), with CDI the most notable form of antibiotic-associated diarrhea.…”
Section: Probioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gut probiotics may be effective for secondary prevention in patients with recurrent Clostridium difficileassociated diarrhea through maintenance of the normal gastrointestinal flora [39]. As reported, Bulleidia could ferment glucose and anti-inflammatory products acetate, lactate, and trace amounts of succinate were the end products of fermentation [40]. A few studies demonstrated that Eubacterium and Bifidobacteria were able to use carbohydrate for the production of short-chain fatty acids, which can inhibit inflammatory responses in the gut [41,42].…”
mentioning
confidence: 99%